THE MECHANISM OF LEGAL REGULATION IN THE CONTEXT OF CIVIL LAW STUDIES - A. S. Grabovets (Гуманитарные и юридические исследования)
The author substantiates the proposition that as a result of legislative changes that the majority of the jurists characterize as corporate reform, the issue of understanding the essence of the mechanism of regulation of corporate relations is topical, as well as the question about the sources of its regulation of the relationship between the norms of civil law and corporate law.